Mapping freshwater snails in north-western Angola: distribution, identity and molecular diversity of medically important taxa - Allan, Fiona (2017)
Background - This study was designed to determine the distribution and identity of potential intermediate snail hosts of Schistosoma spp. in Bengo, Luanda, Kwanza Norte and Malanje Provinces in north-western Angola. This is an area where infection with Schistosoma haematobium, causing urogenital schistosomiasis, is common but little is yet known about transmission of the disease. Angola has had a varied past with regard to disease control and is revitalising efforts to combat neglected tropical diseases. Methods - Snails were sampled from 60 water-contact points. Specimens of the genera Bulinus, Biomphalaria or Lymnaea were screened for trematode infections by inducing cercarial shedding. Snails were initially identified using shell morphology; subsequently a cytochrome c oxidase subunit 1 (cox1) gene fragment was amplified from a subset of snails from each site, for molecular identification. Cercariae were captured onto FTA cards for molecular analysis. Specimens of Bulinus angolensis collected from the original locality of the type specimen have been characterised and comparisons made with snails collected in 1957 held at the Natural History Museum, London, UK. Results - In total snails of nine genera were identified using morphological characteristics: Biomphalaria, Bulinus, Gyraulus, Lanistes, Lentorbis, Lymnaea, Melanoides, Physa and Succinea. Significant for schistosomiasis transmission, was the discovery of Bulinus globosus, B. canescens, B. angolensis, B. crystallinus and Biomphalaria salinarum in their type-localities and elsewhere. Bulinus globosus and B. angolensis occurred in two distinct geographical areas. The cox1 sequence for B. globosus differed markedly from those from specimens of this species collected from other countries. Bulinus angolensis is more closely related to B. globosus than originally documented and should be included in the B. africanus group. Schistosoma haematobium cercariae were recovered from B. globosus from two locations: Cabungo, Bengo (20 snails) and Calandula, Malanje (5 snails). Schistosoma haematobium cercariae were identified as group 1 cox1 corresponding to the type common throughout the African mainland. Conclusions - Various freshwater bodies in north-western Angola harbour potential intermediate snail hosts for urogenital schistosomiasis, highlighting the need to map the rest of the country to identify areas where transmission can occur and where control efforts should be targeted. The molecular phylogeny generated from the samples confirmed that considerable variation exists in B. globosus, which is the primary snail host for S. haematobium in many regions of Africa.